The Evolution of Arebbe: Tradition in the Face of Urban Change - Musthafa, Fera Andriani Djakfar (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2025)
The Arebbe tradition is a form of almsgiving where the reward is intended to be sent to deceased relatives. The procedure involves sending food and dishes to religious figures residing near the executor's residence, as well as requesting prayers for deceased relatives. This tradition continues among the urban Bangkalan community even though geographically, Bangkalan Regency is close to the metropolitan city of Surabaya. This research aims to explore the Arebbe tradition and its procedures, how the tradition persists and evolves, and how it can continue to survive using the concept of the four basic styles of action initiated by John Obert Voll. This research is a descriptive qualitative study with a phenomenological approach. Data collection techniques include unstructured interviews, observation, and documentation. The data analysis technique for this research utilizes the Moustakas model, simplified by Cresswel. The research found that the Arebbe tradition can continue to thrive among the urban Bangkalan community due to four supporting factors: first, adaptationism, such as replacing home-cooked meals with store-bought dishes.; second, the authority of the text as religious legitimacy, with a theological basis or postulates from religious texts supporting the Arebbe tradition; third, conservative action, consisting of advice and messages from elders to continue maintaining Arebbe traditions; fourth, personal aspects or charismatic figures supporting the Arebbe tradition among the urban Bangkalan community